Mastoidectomy: anatomical parameters x surgical difficulty - Pereira, Anastácio Rodrigues, Júnior; Pinheiro, Sebastião Diógenes; de Castro, José Daniel Vieira; Filho, João Aragão Ximenes; de Freitas, Marcos Rabelo (Arquivos Internacionais de Otorrinolaringologia, 2012)
Introduction: The lowered temporal meninges and/ or anterior sigmoid sinus are contiditions that can determine surgical difficulties in performing mastoidectomy.Objective: To correlate in the tomography the extent of the prolapse of the sigmoid sinus and of temporal meninges with the surgical difficulty in the mastoidectomy.Method: The tomographic measurements of prolapse sigmoid and of temporal meninges were correlated with the presence or non-presence of the surgical difficulty observed during the mastoidectomy procedure in patients with ostomatoiditis chronic (n = 30).Form of study: Contemporary cohort transverse.Results: In 10 patients were observed surgical difficulty distributed as: due to prolapse of the sigmoid sinus (n = 2) or temporal meninges prolapse (n = 7) or both (n = 1). In patients in which the surgical difficulty was due to sigmoid sinus prolapse, the tomography distance of the anterior border of the sigmoid sinus to posterior wall of external auditory canal was lower than 9 mm. In patients in which surgical difficulty was due to temporal meninges prolapse, the tomographic distance to the upper plane of the petrous bone was 7 mm.Conclusion: The computerized tomography distance between the temporal meninges and the upper plane of the petrous bone 7 mm and the distance of the anterior border of the sigmoid sinus to posterior wall of external auditory canal was lower than 9 mm are predictive to the surgical difficulties to perform mastoidectomy.
Keywords: tomography; temporal bone; meninges